Approximate Confidence Intervals for the Log‐Normal Standard Deviation. (3rd March 2015) - Tang, Shuhan; Yeh, Arthur B.
Abstract : In this work, approximate confidence intervals are derived for the standard deviation of a log‐normal distribution. Simulations are conducted to evaluate the coverage probability, average length, and coverage bias of the derived approximate confidence intervals. The simulation results indicate that the proposed approximate confidence intervals perform reasonably well when the standard deviation of the log‐transformed variable is small. The approximate confidence intervals are applied to a phase I pharmacokinetic study and a real data set concerning a lab testing of reference engine oil. Copyright © 2015 John Wiley & Sons, Ltd.